Unruly Women and Carnivalesque Countercontrol: Offensive Humor in Mediated Social Protest. (April 2019) - Graefer, Anne; Kilby, Allaina; Kalviknes Bore, Inger-Lise
At the Women's March in January 2018, many protest posters featured offensive jokes at the expense of Trump's body and behavior. Such posters were shared widely online, much to the amusement of the movement's supporters. Through a close analysis of posts on Instagram and Twitter, we explore the role of "vulgar" and "offensive" humor in mediated social protest. By highlighting its radical and conservative tendencies, we demonstrate how we can understand these practices of offensive humor as a contemporary expression of "the carnivalesque" that is complexly intertwined with social change.